Menguak Konsep Kebersandingan Fethullah Gulen dan Asimilasi Budaya Tariq Ramadhan - Ika Yunia Fauzia (Islamica: Jurnal Studi Keislaman, 2009)
The wave of immigration of Muslims to European countries has brought with it the serious consequences as to how these Muslims should adapt culturally and religiously to the entirely different circumstances. Some Muslim intellectuals ?like Fethullah Gulensuggested that Muslims should maintain the cultural co-existence in a way that would not endanger their religious tradition while at the same time bring a state of peace both for themselves and for the communities they live in. Tariq Ramadhan in the meantime suggested that Muslims be committed to what he calls the cultural assimilation whereby they put aside their cultural upbringing from their country of origin and assimilate fully into the cultural live of Europe. Hence, this paper is about the analysis of the cultural dilemma that Muslims face in Europe by referring to the thought of Gulen and Ramadhan on the issue at hand. Although the context of the paper is limited to Europe, the content of the analysis is presented in such a way that it may also be relevant to similar problems faced by Muslims in different cultural and social settings.